TRANSFORMING FIELD EDUCATION: VOICES OF FIELD EDUCATORS IN CANADA - Drolet, Julie; Tettman, Liz; Chand, Tejika; Hameline, Hanna; Kaushik, Vibha; Khatiwada, Kamal; Klassen, Shannon; Chilanga, Emmanuel; McConnell, Sheri; McKee, Eileen; Nicholas, David; Walsh, Christine (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2023)
Social work field educators are facing new challenges and opportunities that require innovative approaches to transform social work field education. Field education is critical to student learning, and in turn, social work practice. In Canada, field education is in crisis, due in part to growing social work student enrolments, government cutbacks to post-secondary education, limited resources, and organizational restructuring, all of which contribute to a reduced number of field placements in agency settings. The objective of this study is to respond to this situation by engaging field educators to better understand what is needed to transform field education in Canada. Researchers asked three to five questions in 31 focus groups discussion sessions with field educators nationally. The responses were coded using thematic analysis. This article presents three themes that are critical to the transformation of field education: innovative practices for field education, impacts of COVID-19, and decolonization of field education. The implications and recommendations call on the collaboration of field education stakeholders across Canada to expand understanding about the critical role of field education in organizations and the profession, and in turn, nurture new field learning opportunities.